Occurrence Mechanism of Large Acceleration in KiK-net Seismic Records during Iwate–Miyagi Nairiku Earthquake in 2008 - Kamagata, Shuichi; Takewaki, Izuru (Frontiers in Built Environment, 2017)
The KiK-net is a vertical array system and seismic motions are recorded at the ground surface and in the borehole. With the peak acceleration of 24.5m/s2 at AKTH04 (EW) and 38.7m/s2 at IWTH25 (UD) during the Iwate-Miyagi Nairiku earthquake in 2008, the occurrence mechanism of large accelerations is investigated by the non-stationary Fourier spectra and the double integrated displacement profile. From the difference in the occurrence time, the frequency and the amplitude of dominant components between the surface and the borehole, it is clear that the amplification in the surface soil caused the large acceleration at the surface. In the deformation process of the surface soil, the whipping mode is picked up at AKTH04. The relative displacement profile between the surface and the borehole is analyzed by the phase curves. The orbit at AKTH04 is identified by the sinusoidal waves of the sway, up-down and rocking modes. It can be concluded that the large accelerations at AKTH04 may be due to an irregular local mode caused by the collision between the base-mat and surrounding soil. From the orbit at IWTH25, the vertical pulse can be regarded as “an induced vertical motion” due to the collision between the base-mat of an observation house and the soil beneath it.